Initial study of low cost crepitus joint degradation finding using acoustic localization - Leong Y.W.; Seki H.; Anuar A.; Nadarajan C.; Jusoh M.H.B.; Jalal M.F.B.A.; See O.H.; Sahari K.S.B.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Costs; Data acquisition; Gradient methods; Microphones; Software engineering; Time difference of arrival; 'current; Acoustic localization; Acoustic method; Aoa (angleof-arrival); Crepitus; Localisation; Low-costs; Medical practitioner; Set-ups; Triboacoustic; Diagnosis